Isu-Isu Hadis Tentang Operasi Plastic - Hefni Julidar; Ardiansyah; Muhammad Nuh Siregar (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Abstract The development of modern medical science has given rise to various medical procedures, one of which is plastic surgery, which is performed not only for medical treatment but also for aesthetic purposes. This phenomenon raises legal and ethical issues in Islam, particularly in relation to the Prophetic traditions that prohibit altering Allah’s creation and those that encourage medical treatment and the removal of harm. This paper aims to examine the issues of hadith related to plastic surgery by analyzing its classification, relevant hadiths concerning prohibition and permissibility, and its legal status based on the maqāṣid al-sharī‘ah approach. This study employs a qualitative library research method, analyzing hadith collections, classical commentaries, and contemporary Islamic jurisprudence literature. The findings indicate that reconstructive plastic surgery intended for medical treatment and the removal of physical or psychological harm is permissible in Islam and may even become obligatory when it relates to the protection of life and human dignity. In contrast, purely cosmetic plastic surgery performed solely for aesthetic purposes without a clear sharī‘ah-based necessity is generally prohibited, as it falls under the category of altering Allah’s creation. Therefore, the legal ruling on plastic surgery in Islam is contextual and must consider its objectives, benefits, and potential harms in accordance with Islamic legal principles. Keywords: plastic surgery, hadith, maqāṣid al-sharī‘ah, alteration of Allah’s creation, Islamic law Abstrak Perkembangan ilmu kedokteran modern telah melahirkan berbagai bentuk tindakan medis, salah satunya operasi plastik, yang tidak hanya digunakan untuk tujuan pengobatan tetapi juga untuk kepentingan estetika. Fenomena ini menimbulkan persoalan hukum dan etika dalam Islam, khususnya terkait hadis-hadis Nabi Muhammad saw. yang membahas larangan mengubah ciptaan Allah serta anjuran untuk berobat dan menghilangkan mudarat. Makalah ini bertujuan untuk mengkaji isu-isu hadis tentang operasi plastik dengan menelaah klasifikasi operasi plastik, hadis-hadis yang berkaitan dengan larangan dan kebolehan, serta menganalisis hukumnya berdasarkan pendekatan maqāṣid al-syarī‘ah. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan kepustakaan (library research), melalui analisis terhadap sumber-sumber hadis, kitab syarah, dan literatur fikih kontemporer. Hasil kajian menunjukkan bahwa operasi plastik yang bersifat rekonstruktif dan bertujuan untuk pengobatan serta penghilangan mudarat dibolehkan dalam Islam, bahkan dapat menjadi wajib apabila berkaitan dengan keselamatan jiwa dan kehormatan manusia. Sebaliknya, operasi plastik kosmetik murni yang dilakukan semata-mata untuk tujuan estetika tanpa kebutuhan syar‘i yang jelas cenderung dilarang karena termasuk dalam kategori mengubah ciptaan Allah. Dengan demikian, penetapan hukum operasi plastik bersifat kontekstual dan harus mempertimbangkan tujuan, maslahat, serta mudarat yang ditimbulkan sesuai dengan prinsip syariat Islam. Kata kunci: operasi plastik, hadis, maqāṣid al-syarī‘ah, taghyīr khalqillāh, hukum Islam